A panchronic view at the pronoun you: portraits from the past to the present that supported a sociofunctional study - Rocha, Warley José Campos (2021)
The pronoun você (you) are the protagonist in many studies when it comes to the description of Brazilian Portuguese. In this article, we aim to present the socio-historical path of the pronoun você, highlighting its grammaticalization process caused by the pressures of use over time, highlighting the social factors that influence this process and verifying how this item is registered in historical, prescriptive and descriptive grammars. In methodological terms, the text was developed from a bibliographical review, whose bases are briefly found in a sociofunctional study developed in a speech community in the interior Bahia state. Finally, we concluded that socio-historical investigation is important, as well as the observation of how grammarians record the item that a sociofunctionalist is interested in studying, as we can observe both the grammaticalization process and the phenomena of linguistic variation and change arising from it.